Pengaruh Kualitas Pelayanan dan Citra Bank Terhadap Kepuasan Nasabah BNI KCU Parepare - Nurul Riska Ainun; Syamsuriani; Siti Diva Syarifah Lukman (STIE Amkop Makassar, 2024)
This study aims to determine the effect of service quality and bank image on BNI KCU Parepare customer satisfaction. This research is quantitative research with the analysis technique used is multiple linear regression. The sampling technique used the Slovin method, with a sample taken of 136. The results showed that service quality and bank image had a significant positive effect on BNI KCU Parepare customer satisfaction, both partially and simultaneously.